Outcome of underlay versus interlay tympanoplasty in patients with inactive mucosal chronic otitis media with large central perforation: a retrospective comparative study - ., Rajneesh; Valse, Dinesh; Pawar, Shradha; Doddamani, Anil Kumar (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Aim and objective were to study the outcome of underlay versus interlay tympanoplasty in patients with inactive mucosal chronic otitis media with large central perforations in terms of graft uptake rate and hearing improvement. Methods: The present study was conducted retrospectively on 110 patients of inactive mucosal chronic otitis media with large central perforation, 55 patients selected from each group undergoing underlay or interlay technique in a tertiary referral hospital, Department of ENT, ESIC Kalaburagi, Karnataka, from February 1 2018 to January 31, 2020. Results: Total 110 patients were included in the study. Male:female ratio was 1:2.2. The age group in this study ranged from 13-50 years of age. Preoperative mean air bone gap in groups A and B was 30.28±6.62, and 30.18±6.87 dB and postoperative mean air bone gap was 19.44±7.66 and 15.13±6.3 dB. In both the groups a significant mean reduction in air bone gap was observed. Mean reduction was maximum in group B. Statistically, intergroup difference in reduction in air bone gap was highly significant (p<0.001). Graft success rate being 89.09% and 94.54% in underlay (group A) and interlay (group B) respectively. Conclusions: Interlay is a better technique than underlay in chronic otitis media inactive mucosal disease with large central perforation in terms of hearing improvement and graft uptake.